Cardiovascular event rates increase after each recurrence and associate with poor statin adherence. (7th July 2020) - Lassenius, Mariann I; Toppila, Iiro; Bergius, Susanne; Perttilä, Julia; Airaksinen, K E Juhani; Pietilä, Mikko
Abstract: Aims: The study evaluated the quality of cardiovascular prevention in real-world clinical practice. The recurrence of up to five cardiovascular events was assessed, as data on recurrence beyond the first event and interindividual variations in event rates past the second event have been sparse. Low-density lipoprotein cholesterol concentrations and lipid-lowering therapy use were investigated. Methods: This retrospective register-based study included adult patients with an incident cardiovascular event between 2004 and 2016 treated in the hospital district of southwest Finland. Patients were followed for consecutive cardiovascular events or cardiovascular death, low-density lipoprotein cholesterol and statin purchases. The timing of event recurrence was evaluated, and predictive factors were assessed. Results: A wide interindividual variation in cardiovascular event recurrence was observed, each additional event caused an increased risk, the median time of recurrence decreased from 7 to one year for the second and fifth event. Event rates increased correspondingly from 12 to 43/100 patient-years and were most pronounced in the first years following the previous event. The low-density lipoprotein cholesterol goal (<1.8 mmol/l) was reached by 18% in the year after the event and statin underuse was associated with an increased risk of recurrence. Six months after the index event high intensity statins were used by only 22% of the cohort. Conclusion: The study provides new perspectives on individual risk assessment showing that event rates are not stable for all patients but increase 1.2–1.9-fold per consecutive event. The underuse of statins and poor adherence support the identification of these patients for intensified multifactorial preventive measures.